Questionnaire pour l'Elaboration de Scénarios de Prospective Stratégique sur la Sécurité Alimentaire et la Transition Agroécologique en Tunisie à l'horizon 2050 - Sghaier, Mongi; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2024)
The objective of this questionnaire is to solicit stakeholders' insights on salient aspects of food security and agro-ecological transition (AET) in Tunisia. The questionnaire is designed to address the formulation of the central scenario question, identify critical influencing factors and drivers, prioritize them based on their relative importance and uncertainty, and explore future trends that may shape food security and the agroecological transition of agri-food systems in Tunisia by the year 2050. The questionnaire is intended to be utilized in the preliminary stages of strategic foresight scenario development. During these early stages, the objective is to ascertain the experts' insights regarding the prevailing and prospective catalysts of change and transformation. This approach serves as a foundational step in the overall scenario’s development process.